Islamic insurance model revisited: Operationalizing the business paradigm within the Shari’ah parameters / Fatima Abdelwahab Galal - Abdelwahab Galal, Fatima (Institute of Graduate Studies, UiTM, 2016)
This thesis revisited the Islamic insurance models’ operations and its various business paradigms within the Shari’ah parameters in three different countries which are Bahrain, Malaysia, and Sudan. Although, the Islamic insurance industry is experiencing a period of rapid growth in terms of its net contributions and profit, amidst tough obstacles and constraints due to the Shar’iah issues in certain aspects. Islamic insurance operations require finetuning in line with Islamic jurisprudence and Muslims need. There are many different operational models with various Islamic jurisdictions trying to meet the needs of Muslims in general as regard Islamic insurance in the global Islamic economy. However, each of these models has its own advantages and disadvantages. Moreover, there is no agreement amongst the Islamic scholars on which of these models can be considered the best. This means different organizations use the same Islamic contract but with different applications. These models, which are Wakalah, Mudarabah, Waqaf and the Hybrid model, have several shortcomings that need to be studied and addressed to strengthen global Islamic insurance industry. The two challenging issues that are studied are the ownership of the Islamic insurance risk fund or the contribution fund and the surplus distribution accumulated from the risk fund. There are differences of opinion regarding Shari’ah compliance of certain practices. This has led to layers of regulatory differences in countries like Bahrain, Malaysia, and Sudan, resulting in initiation of separate regulatory frameworks for Islamic insurance as a medium to ensure rapid growth and encourage Islamic insurance. This study adopts MANOVA because there are multiple dependent variables as well as independent variables within the constructs of the research…